2020
DOI: 10.1101/2020.06.01.20119651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic variants of PIEZO1 associate with COVID-19 fatality

Abstract: COVID-19, caused by the SARS-CoV-2 virus, carries significant risk of mortality and has spread globally with devastating societal consequences. Endothelial infection has been identified as a feature of the disease and so there is motivation to determine the relevance of endothelial membrane mechanisms affecting viral entry and response. Here, through a study of patient data in UK Biobank released on 16 April 2020, we suggest relevance of PIEZO1, a non-selective cation channel protein that both mediates endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…There is evidence that membrane proteins such as ACE2 and TMPRSS2 are important in SARS-CoV-2 entry[ 54 , 101 ]. It is indisputable that viral entry is affected by other membrane proteins and lipids[ 102 , 103 ].…”
Section: Genetic Association Studies and Covid-19 Host Genetics Initiativementioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that membrane proteins such as ACE2 and TMPRSS2 are important in SARS-CoV-2 entry[ 54 , 101 ]. It is indisputable that viral entry is affected by other membrane proteins and lipids[ 102 , 103 ].…”
Section: Genetic Association Studies and Covid-19 Host Genetics Initiativementioning
confidence: 99%
“…A genome sequence analysis showed that these SNPs vary in prevalence with ethnicity and that the most significant SNP (rs7184427) varies between 65% to 90%. The analysis also suggests that rs7184427 affects a residue that is highly evolutionarily conserved and therefore has functional importance for COVID-19 severity and fatality[ 101 ].…”
Section: Genetic Association Studies and Covid-19 Host Genetics Initiativementioning
confidence: 99%
“…A possible explanation of the substantial variation in susceptibility to SARS-CoV-2 virus and the wide unpredictability in COVID-19 manifestation is the variability in the host genetic background. In fact, emerging genome-wide association [17,18] and candidate gene association [19] studies have revealed an association between a host genetic risk factor and the severity of COVID-19 illness.…”
Section: Introductionmentioning
confidence: 99%